Implementasi Pembelajaran Fisika SMA dengan Melibatkan Kecerdasan Intrapersonal dan Interpersonal: Implementation of Physics Learning by Engaging Intrapersonal and Interpersonal Intelligence - Pertiwi, Novia Ayu Sekar (SEJ (Science Education Journal), 2018)
This study purposed to improve student learning outcomes in understanding vector material using physics learning media that involve intrapersonal and interpersonal intelligence. The results showed that more than 70% of students completed with completeness between70.42 - 97.18 in vector material. Based on the results of the study it can be concluded that the Physics learning media involving intrapersonal and interpersonal intelligence can be used as an alternative learning for students at Plumpang High School.